Human subthalamic nucleus – Automatic auditory change detection as a basis for action selection. (4th July 2017) - Heldmann, Marcus; Münte, Thomas F.; Paracka, Lejla; Beyer, Frederike; Brüggemann, Norbert; Saryyeva, Assel; Rasche, Dirk; Krauss, Joachim K.; Tronnier, Volker M.
Highlights: Subthalamic nucleus receives information about auditory irregularities. Global as well as local irregularities are represented by the STN. Information about irregularities might prepare the motor system for action. Abstract: The subthalamic nucleus (STN) shapes motor behavior and is important for the initiation and termination of movements. Here we ask whether the STN takes aggregated sensory information into account, in order to exert this function. To this end, local field potentials (LFP) were recorded in eight patients suffering from Parkinson's disease and receiving deep-brain stimulation of the STN bilaterally. Bipolar recordings were obtained postoperatively from the externalized electrode leads. Patients were passively exposed to trains of auditory stimuli containing global deviants, local deviants or combined global/local deviants. The surface event-related potentials of the Parkinson's patients as well as those of 19 age-matched healthy controls were characterized by a mismatch negativity (MMN) that was most pronounced for the global/local double deviants and less prominent for the other deviant conditions. The left and right STN LFPs similarly were modulated by stimulus deviance starting at about 100 ms post-stimulus onset. The MMN has been viewed as an index of an automatic auditory change detection system, more recently phrased in terms of predictive coding theory, which prepares the organism for attention shifts and for action. The LFP-data from the STN clearly demonstrate that the STN receives information on stimulus deviance, possibly as a means to bias the system to interrupt ongoing and to allow alternative actions.